Pengaruh Net Ekspor Dan Nilai Tukar terhadap Cadangan Devisa Indonesia Periode 2010 - 2023 - Sinaga, Martina Apriani; Syapsyan, Syapsyan; Sidabalok, Supriani (Universitas Mataram, 2025)
Indonesia adheres to an open economic system, which has a close relationship with international trade activities. International trade plays a role in helping countries fulfill various domestic needs. To finance international trade activities, Indonesia relies on sources of funds derived from foreign exchange reserves. The study aims to determine the effect of net exports and the rupiah exchange rate on Indonesia's foreign exchange reserves for the period 2010-2023. Using time series data for the period 2010-2023, multiple linear regression analysis methods using the eviews 12 program. The results show that partially net exports and the rupiah exchange rate have a positive and significant effect on foreign exchange reserves. Simultaneously net exports and exchange rates have a significant effect on foreign exchange reserves. With an adjusted R-Square value of 0.746679, which means that 74.66% of the foreign exchange reserves variable can be explained by the independent variables in the study while 25.34% is explained by other variables outside the research model.